SARS-CoV-2 Causes a Systemically Multiple Organs Damages and Dissemination in Hamsters - Song, Zhiqi; Bao, Linlin; Yu, Pin; Qi, Feifei; Gong, Shuran; Wang, Jie; Zhao, Binbin; Liu, Mingya; Han, Yunlin; Deng, Wei; Liu, Jiangning; Wei, Qiang; et al. (Frontiers in Microbiology, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has spread across the world and impacted global healthcare systems. For clinical patients, COVID-19 not only induces pulmonary lesions but also affects extrapulmonary organs. An ideal animal model that mimics COVID-19 in humans in terms of the induced systematic lesions is urgently needed. Here, we report that Syrian hamster is highly permissive to SARS-CoV-2 and exhibit diffuse alveolar damage and induced extrapulmonary multi-organs damage, including spleen, lymph nodes, different segments of alimentary tract, kidney, adrenal gland, ovary, vesicular gland and prostate damage, at 3-7 days post inoculation (dpi), based on qRT-PCR, in situ hybridization and immunohistochemistry detection. Notably, the adrenal gland is a novel target organ, with abundant viral RNA and antigen expression detected, accompanied by focal to diffuse inflammation. Additionally, viral RNA was also detected in the corpus luteum of the ovary, vesicular gland and prostate. Focal lesions in liver, gallbladder, myocardium, and lymph nodes were still present at 18 dpi, suggesting potential damage after disease. Our findings illustrate systemic histological observations and the viral RNA and antigen distribution in infected hamsters during disease and convalescence to recapitulate those observed in humans with COVID-19, providing helpful data to the pathophysiologic characterization of SARS-CoV-2-induced systemic disease and the development of effective treatment strategies.